The Implementation Of Mind Mapping Technique to Improve Students Understanding in English Morphology - Mei Hardiah (AL LUGHAH, 2019)
This study aims to know how far the application of Mind Mapping technique is capable to improve   students understanding on theoretical course such as English Morphology.The  method of the research is experiment with queasy experiment applying nonequivalent control group design . Population of this research are odd semester students (3rd semester) who take lecture on English Morphology course. There are two classes’ namely experimental class which is treated with mind mapping technique and control class which is taught conventionally. After applying mind mapping technique in experimental class, the result is significantly different. The experiment class achievement from the test is better than the result of the test in the control class. Moreover based on the observation, the students from the class treated with mind mapping technique proved to be more motivated and enthusiastic in understanding the material. Student’s center is also implemented in experimented class.